Spectrophotometric determination of azithromycin in tablets. An alternative method for application in the pharmaceutical industry - Gonzales Condori, Elvis Gilmar; Huaman Cruz, Mary Luz; Llamocarevilla, Alex Luis; Gonzales Condori, Jonathan; Alvarez Gonzales, Rosa (LACCEI, 2025)
In the present research, a simple spectrophotometric method for quantifying azithromycin in tablets was validated. For this purpose, validation parameters established by the United States Pharmacopoeia (USP) were evaluated. The results show that the method is linear with a coefficient of determination of 0.9995, precise with relative standard deviations ranging from 0.18% to 0.25%, and accurate with a recovery percentage of 97.75%. Likewise, four brands of azithromycin commonly sold in the city of Arequipa, Peru, were analyzed and found to comply with the uniformity of azithromycin content of 500 mg. In conclusion, the developed method could be considered by pharmaceutical laboratories, quality control laboratories, or universities to perform routine or educational tests to quantify azithromycin in tablets.